Characteristics, clinical outcome, and prognostic significance of IDH mutations in AML. Issue 8 (August 2015) - DiNardo, Courtney D.; Ravandi, Farhad; Agresta, Sam; Konopleva, Marina; Takahashi, Koichi; Kadia, Tapan; Routbort, Mark; Patel, Keyur P.; Mark Brandt; Pierce, Sherry; Garcia‐Manero, Guillermo; Cortes, Jorge; et al.
<x xml:space="preserve">Abstract</x> The pathophysiology of IDH mutations in tumorigenesis is increasingly described, yet the prognostic significance of IDH1 and IDH2 mutations in AML remains controversial. The primary objective of this study was to define the natural history and prognosis of patients with AML and IDH1 or IDH2 mutations and provide historical survival expectations. A total of 826 patients treated from 2010 to 2014 at a single institution were evaluated, including 167 patients (20%) with AML and IDH1 or IDH2 mutations. Median age was 62 years (range 18–92). There were 59 IDH1‐R132, 83 IDH2‐R140, and 23 IDH2‐R172 mutations. Clinicopathologic characteristics associated with IDH‐mutations included older age, less frequent therapy‐related status, and increased incidence of intermediate‐risk cytogenetics, FLT3‐ITD mutations, and NPM1 mutations. Remission rates (CR/CRi) by AML treatment status were: induction, 68%; Salvage‐1 (S1), 42%; and Salvage‐2 and beyond (S2+), 27%. No difference in response was identified by IDH mutation status. Similarly, overall survival (OS) was not dependent on IDH status within any cohort. The median OS was 15.4 months in induction, 8.7 months in S1, and 4.8 months in S2+. This analysis defines the clinical outcome associated with IDH‐mutations in both the front‐line and salvage AML treatment settings, and confirms that response rate and OS for both IDH‐mutated and IDH wild‐type AML patients is comparable. This provides contemporary data to be used for comparison with results of novel investigational (e.g., selective IDH inhibitor) strategies. Am. J. Hematol. 90:732–736, 2015. © 2015 Wiley Periodicals, Inc.